Anxiety and depression in patients with haematological neoplasms in Malaysia - Ng, Diana Leh-Ching; Gin, Gin Gan; Yeh, Chwan Leong; Ping, Chong Bee; Fui, Edmund Min Chin; Habibah, Abdul Halim; Tengku Ahmad Hidayat, Tengku Aziz,; Henning, Loo; Teh, Alan K. H. (Malaysia Medical association, 2019)
ABSTRACT